Early Career Outcomes of Embedded Research Fellows: An Analysis of the Health System Impact Fellowship Program - Bahar Kasaai; Erin Thompson; Richard Glazier; Meghan McMahon (Kerman University of Medical Sciences, 2023)
Background  This descriptive study reports the early career outcomes of postdoctoral fellows who completed a novel embedded fellowship training program, the Canadian Institutes of Health Research (CIHR) Health System Impact (HSI) Fellowship. The program was designed to support impact-oriented career paths of doctoral graduates, build research capacity within health system organizations (HSOs), and help to advance learning health systems (LHSs) in Canada.Methods  Employment of fellowship alumni upon completion of the program was tracked using internet searches of publicly accessible online sources and complemented with program survey data.Results  Descriptive analyses show that all 87 eligible alumni included in the study are currently employed (100% of 87), with 92% employed in Canada. Their employment spans several sectors, including in academic (37%), public (29%), healthcare delivery (17%), and private (14%) sectors. Altogether, 32% of alumni hold hybrid roles with an affiliation in academia and another sector. The most common position types are senior scientist (42%), professorships (18%), and director, manager or administrator roles (12%). Program reporting data indicate that these employment outcomes are generally consistent with the group's career aspirations reported at the start of the fellowship program, and that the program receives high ratings from fellows in the extent it is believed to support their career preparedness and readiness (4.49 out of 5).Conclusion  This study finds that HSI Fellow alumni are employed mostly in research-related roles in a range of sectors including, but not limited to, academia, and that they positively perceive the program's success in elevating their career readiness and potential to make an impact - suggesting that the program may help equip fellows with the skills, readiness and networks for contribution in a broad array of employment sectors and roles. The findings are a promising signal of the demand for research talent and the growing capacity for LHSs in Canada.